IMPLEMENTATION OF E-COMMERCE CERAMIC SHOP USING APPLICATION PROGRAMMING INTERFACE WITH JSON WEB TOKEN AUTHENTICATION - Mepa Kurniasih; Agung Alam Putra; Eka Anggara (Penelitian dan Pengembangan Ilmu, 2025)
CV. Apuy Stone is a ceramic and granite distribution company located in Serang, Banten. One of the problems faced is the accumulation of goods in the warehouse due to a mismatch between customer demand and the amount of available stock. Often, products that customers are interested in are not available, while other products pile up and remain unsold for a long time. Based on these conditions, the purpose of this Internship Lecture is to design an information system-based solution that can help the company manage inventory more efficiently. The methods used include direct field observation, interviews with related parties, and analysis of sales transaction data for the past two years. The author built a web-based application using the Laravel framework and MySQL database that aims to process sales data and provide recommendations on inventory. This application is designed to identify products with a low turnover rate (slow-moving) and products with a high level of demand, and assist management in planning more targeted procurement of goods. The results of the system implementation show an increase in accuracy in decision-making related to stock management and a decrease in the number of items piling up unsold. In conclusion, the information system developed can be an effective tool in inventory control based on historical sales data. The benefits of compiling this KKP are directly felt by the company in the form of warehouse operational efficiency, as well as contributing to the development of information technology solutions in the world of small and medium businesses.